2010
DOI: 10.1021/nn101468e
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism of Atomic Manipulation: Bond-Selective Molecular Dissociation via Thermally Activated Electron Attachment

Abstract: We report a new mechanism of (bond-selective) atomic manipulation in the scanning tunneling microscope (STM). We demonstrate a channel for one-electron-induced C-Cl bond dissociation in chlorobenzene molecules chemisorbed on the Si(111)-7 × 7 surface, at room temperature and above, which is thermally activated. We find an Arrhenius thermal energy barrier to one-electron dissociation of 0.8 ± 0.2 eV, which we correlate explicitly with the barrier between chemisorbed and physisorbed precursor states of the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 36 publications
3
39
1
Order By: Relevance
“…While the physisorption energy agreed quite well with the experiment at that time (see Ref. [7] and references therein), the chemisorption energy seemed to be too high compared to 1.0 eV derived from thermal desorption spectra [26] assuming first-order kinetics and a pre-exponential factor of 10 13 s −1 . Also, periodic DFT calculations [22] using a 2×2 mimic surface reported 1.2 eV chemisorption energy.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…While the physisorption energy agreed quite well with the experiment at that time (see Ref. [7] and references therein), the chemisorption energy seemed to be too high compared to 1.0 eV derived from thermal desorption spectra [26] assuming first-order kinetics and a pre-exponential factor of 10 13 s −1 . Also, periodic DFT calculations [22] using a 2×2 mimic surface reported 1.2 eV chemisorption energy.…”
Section: Introductionsupporting
confidence: 76%
“…the breaking of DNA strands [6]. Therefore, a lot of elementary reaction steps like dissociation [7], desorption [8], bond formation [9] and the switching of molecules [10][11][12] between metastable states have been studied with and induced by STM.…”
Section: Introductionmentioning
confidence: 99%
“…Electron-induced surface chlorination of silicon by chlorobenzene has been studied in detail by Palmer, Sloan, and co-workers who showed that, though LAR and directed C−X bond-rupture were prevalent near threshold, the spread in distance and direction of the reacting Cl increased with increasing energy. 13,14 Similar considerations might suggest that localization of reaction would dominate even at metal surfaces, which are much smoother than a semiconductor. The evidence has until now been sparse.…”
Section: ■ Introductionmentioning
confidence: 88%
“…The background to our encounter with non‐local manipulation was a systematic atomic manipulation study of chlorobenzene chemisorbed on the Si(111)‐7×7 surface, which showed a diversity of reactions induced by the scanning tunnelling microscope (STM) tunnelling current, including desorption, diffusion, and C–Cl dissociation. We found, for example, that scanning the silicon surface at low voltage (below +1 V sample bias) had no effect on the molecules, but increasing the STM bias to +2.2 V resulted in chlorobenzene desorption, and proved that this was due to the tunnelling current .…”
Section: Introductionmentioning
confidence: 99%